2018
DOI: 10.1002/jib.479
|View full text |Cite
|
Sign up to set email alerts
|

Biovalorization of brewers’ spent grain for the production of laccase and polyphenols

Abstract: Brewers’ spent grain (BSG) is the main solid by‐product of the brewing process and is typically disposed of as cattle feed. In this study, BSG was evaluated as a substrate for the production of polyphenols and the lignin‐degrading enzyme laccase using fungal solid‐state fermentation by Trametes versicolor. Laccases are finding increasing applications in the food industry and polyphenols have benefits for human health. After 14 days of fermentation with T. versicolor, there was a 3.4‐fold increase in the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
2
19
0
2
Order By: Relevance
“…The fructose content, during the biotreatment with T. versicolor, increased from 0.48 up to 20.9 mg/g db. This is in agreement with our previous study, where it was shown that T. versicolor has higher affinity towards glucose than fructose [43,45].…”
Section: Parameters Of Analysissupporting
confidence: 94%
See 4 more Smart Citations
“…The fructose content, during the biotreatment with T. versicolor, increased from 0.48 up to 20.9 mg/g db. This is in agreement with our previous study, where it was shown that T. versicolor has higher affinity towards glucose than fructose [43,45].…”
Section: Parameters Of Analysissupporting
confidence: 94%
“…During the biotreatment, the sucrose content decreased continuously, and after 10 days of cultivation, the amounts of sucrose were 3.73 mg/g db and 0.29 mg/g db for the hull-less pumpkin oil cake in case of the bio-treatment with T. versicolor and H. grisea, respectively. This is in agreement with our previous study, where it was shown that T. versicolor has higher affinity towards glucose than fructose [43,45]. In the first two days of flaxseed oil cake bio-treatment, the sucrose was not recorded.…”
Section: Decreased Bysupporting
confidence: 93%
See 3 more Smart Citations